NOTES ON TWO LEGUMINOUS GENERA FROM EASTERN INDONESIA - A. J. G. H. KOSTERMANS (REINWARDTIA, 1952)
1. A new monotypic genus, Kalappia Kostermans, is established for a tree of commercial importance from Celebes, K. celebica Kostermans. The genus is assigned to Caesalpiniaceae (Tribus Cassiae).2. The Papilionaceous genus Desmofischera Holth.(only species: D.monosperma Holth.) is reduced to a synonym of Monarthrocarpus Merr.[only species: M. securiformis (Benth.) Merr.]. Additional collections, from Morotai, are cited.